EFEKTIFITAS PROGRAM USAHA EKONOMI KELURAHAN- SIMPAN PINJAM (UEK-SP) MINAS SERUMPUN DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT DI KELURAHAN MINAS JAYA KECAMATAN MINAS KABUPATEN SIAK - Indriani, Yulfita; Gusnardi, Gusnardi; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study aims to determine the effectiveness of the Savings and Loans Economic Business Program (UEK-SP) in Improving Community Economic Welfare in Minas Jaya Village, Minas Subdistrict, Siak Regency, and to find out what factors are supporting and inhibiting the implementation of the Urban Economy-Save Business Program Borrowing (UEK-SP) in improving the economic welfare of the community in Minas Jaya Sub-District, Minas District, Siak Regency. Informants in this study were the Chairperson of UEK-SP Minas Serumpun, the Cashier Staff of UEK-SP Minas Serumpun, and the Community (Utilizers) who were directly involved in the implementation of the UEK-SP program or active members of UEK-SP. There are 2 types of data used in this study, namely primary data and secondary data, primary data taken through key informants and informants. The selection of key informants used a purposive sampling technique, in this case the key informant was the chairman of the UEK-SP Minas Serumpun and several staff and cashiers of UEK-SP Minas Serumpun. Whereas the selection of informants used the assisted sampling technique, and those who became informants were people who were directly involved in implementing the UEK-SP program or active members of UEK-SP. Secondary data is obtained through a second source or indirectly through reports, books, or processed data. Based on the results of the study, it was found that the implementation of the Savings and Loan Village Economic Business Program (UEK-SP) of Minas Serumpun Kelurahan Jaya Jaya could be categorized as implemented smoothly but was less effective, this was seen from the indicators used to see the effectiveness of the UEK-SP program namely input, output, process and outcame.Keywords: Effectiveness, distribution of UEK-SP funds, Saving and Borrowing Village Economic Programs (UEK-SP), Empowerment